The Role of Mediterranean Fever Mutation in the Clinical Course and Pathogenesis of Ankylosing Spondylitis - Ali Erhan ÖZDEMİREL,; Hatice Rana ERDEM,; Barış NACIR,; Aynur KARAGÖZ, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate the role of Mediterranean fever (MEFV) gene mutations in the pathogenesis and clinical progression of disease in ankylosing spondylitis patients. Patients and methods: The study included 88 patients (60 males, 28 females; mean age 38.7±8.7 years; range 19 to 56 years) diagnosed with ankylosing spondylitis according to modified New York criteria. The patients were evaluated for peripheral joint and hip joint involvement and treatment characteristics. Using multiplex/polymerase chain reaction reverse hybridization method, the presence of 12 different MEFV mutations was investigated. Results: Of 29 patients, heterozygote mutation was detected in 24 (83%), mutations in both alleles were detected in three (10%), and combined heterozygote mutations were detected in two patients (7%). Three most common mutations were M694V (11.3%), E148Q (8%), and V726A (4.5%). In the group with mutations, symptoms had started earlier than in the other group, and the number of peripheral joints involved was higher. When both characteristics were compared with the characteristics of the group that did not have any gene mutations, the differences were statistically significant (p<0.001 and p=0.044, respectively). The highest correlation with the number of peripheral joints involved was determined for M694V mutation (p=0.034), while onset of symptoms at younger age was correlated with E148Q mutation (p=0.010). Conclusion: Based on the findings of this study and our clinical experience, it can be said that the clinical progression of ankylosing spondylitis patients with MEFV gene mutations is more severe, and this suggests that MEFV gene mutations may be contributive to ankylosing spondylitis pathogenesis.